Mecanismos de resistência ao ácaro rajado em genótipos de tomateiro com altos teores de acil-açúcares - Lucini, Tiago (2013)
The control of two spotted spider mite, Tetranychus urticae , in tomato culture is basically done with chemical applications, and a viable alternative is the development of cultivars with satisfactory levels of resistance. However, research is necessary to seek resistance sources and determine what are the mechanisms and causes involved in this resistance. This study aimed to determine the mechanism of resistance to two spotted spider mite presented by tomato genotypes with high contents of acyl sugars (AA). The evaluated genotypes were to cultivate commercial Redenção (Solanum lycopersicum , with low content of AA and susceptible to mite), accession wild LA-716 (Solanum pennellii, with high content of AA and resistant to mite), one plant of the F1 generation derived the interspecific crossing between Redenção x LA-716, two genotypes of the F2 generation selected with high content of AA (RVTA-2010pl#31 and RVTA-2010pl#94) and two genotypes of the F2 generation selected with low content of AA (RVTA-2010pl#33 and RVTA-2010pl#73). In order to determine the mechanism of resistance, were performed no-choice and free choice tests and also the study of the biological parameters of the mite. Were also determined the density and type of foliar trichomes in the abaxial and adaxial surfaces and their correlations with the content of AA and the parameters evaluated. The selected genotypes with high content of AA (S. pennellii LA-716, RVTA-2010pl#31 and RVTA-2010pl#94) were the least preferred by the two spotted spider mite in the free choice test to remain and o vipositing, showing that these genotypes showed resistance of non-preference. These same genotypes showed high mortality of adult female mites in no-choice and oviposition tests and total mortality of nymphs in the biology test. Furthermore, there was reduction in the rate of oviposition in all tests. In the study of biological parameters there was significant prolong ation of the incubation period egg and reduction viability. Therefore, it is possible to infer that the mechanism of antibiosis also is involved in the resistance of these genotypes to the two spotted spider mite. The highest density of glandular trichomes type IV was observed in the genotypes with high content of AA. The correlation between the content AA in leaflets and density of glandular trichomes was high and significant. The density of glandular trichomes was positively correlated with mortality mite and negatively with its oviposition.